Very Low Density Lipoprotein Metabolism in Patients with Chronic Kidney Disease - Wang, Xuewen (S. Karger AG, 2012)
BACKGROUND: Hypertriglyceridemia is a common metabolic complication of chronic kidney disease (CKD) and an important risk factor for coronary heart disease in this patient population. The mechanisms responsible for the development of hypertriglyceridemia in subjects with CKD are not clear. METHODS: We studied very low density lipoprotein triglyceride (VLDL-TG) and VLDL-apolipoprotein B-100 (VLDL-apoB-100) kinetics in vivo in 6 subjects with non-dialysis-dependent CKD (CKD-ND), 6 subjects with CKD treated with peritoneal dialysis (CKD-PD) and 24 sex-, age- and body mass index-matched control subjects with normal renal function (12 control subjects each matched with the CKD-ND and CKD-PD group, respectively). RESULTS: The secretion rates of VLDL-TG and VLDL-apoB-100 into plasma were not different between CKD-ND or CKD-PD and their respective control groups. The mean residence times of VLDL-TG and VLDL-apoB-100 in plasma, which represents the time VLDL-TG and VLDL-apoB-100 spend in the circulation after secretion by the liver, tended to be greater in subjects with CKD-ND than in control subjects (222 ± 38 vs. 143 ± 21 min, p = 0.07, and 352 ± 102 vs. 200 ± 20 min, p = 0.06, respectively) and were about two-fold greater in subjects with CKD-PD compared with their control group (248 ± 51 vs. 143 ± 21 min and 526 ± 116 vs. 182 ± 16 min, respectively; both p ≤ 0.01). CONCLUSION: Impaired plasma clearance of VLDL-TG and VLDL-apoB-100 is the major abnormality associated with hypertriglyceridemia in patients with either CKD-ND or CKD-PD.